(untitled) (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To find out the pattern of urogenital fistula. Methods: This was a retrospective study of 222 patients who underwent fistula surgery during the period of January 2012 to March 2018 in Kathmandu Model Hospital. The data were collected from the hospital records. The fistulae were classified according Goh system. Patients’ demography, obstetric characteristics and surgical outcome were reviewed. The primary outcome was in terms of urinary continence. Results: Among 222 cases, majority of the patients had fistula due to obstetrical cause, contributing 58% (n=127) and 42% (n=95) had fistula after gyanaecological surgery. The age ranged from 15 to 65 years. Most of the patients had fistula of type 1a, contributing 38% (n=84) and only 0.01% (n=3) of type 3c and 4b according to Goh’s classification. Hundred (78.7%) cases of obstetric fistula patients were dry and continent after surgery, whereas 95(89.4%) cases of fistula after gynecological surgery were successfully repaired. Eighteen patients with obstetric fistula and 6 patients with fistula after gynecological surgery had failed repair. Conclusions: Our study showed obstructed and prolonged labor was the major cause of obstetric fistula, but fistula resulting after gynecological surgery should not be overlooked. Keywords: fistula, iatrogenic, labour